FAKTOR PENENTU NILAI PERUSAHAAN: STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI - Poerwati, Rr. Tjahjaning; Nurhayati, Ida; Kartika, Andi (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2023)
This study aims to test and analyze the effect of Profitability, Capital Structure, Dividend Policy, and Firm Growth on Firm Value in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The data used is in the form of secondary data obtained from the firm's financial statements. This study used purposive sampling techniques with a total sample of 63 companies that met the criteria from 2018 to 2020. The regression model used in this study is a multiple linear regression model. The results showed that Profitability and Dividend Policy have a positive and significant influence on the value of the firm. The Capital Structure has a positive and insignificant influence on the value of the firm. Meanwhile, Firm Growth has a negative and insignificant influence on Firm Value.